A follow-up note on the plausibility of the Leontief and Ghosh closed models. Issue 1 (2nd January 2020) - Manresa, Antonio; Sancho, Ferran
ABSTRACT: Herein we consider Leontief and Ghosh models that partly endogenize both part of final demand and part of value-added. We use Osterhaven's [(2012) Adding Supply-driven Consumption Makes the Ghosh Model Even More Implausible. Economic Systems Research, 24, 101–111] numerical three-sector example to show that anomalies of the sort he finds for a Ghosh closed model can also be found in the closed version of a Leontief model. By assuming, as Oosterhaven did, that aggregate exogenous resources are fixed, we obtain mirror results to his in a Ghosh setting, albeit in the more-traditional Leontief instance. Such numerical anomalies for the three-sector case turn out to be generic to both partially closed models for any 2×2 input–output model. A proof for the general n × n case remains to be uncovered.